PENGARUH PENAMBAHAN BAHAN PELAPIS (MOCAF, TEPUNG BERAS DAN CMC) TERHADAP TINGKAT KESUKAAN KERIPIK BAYAM MERAH (Amarathus Tricolor L.) - Maryati; Artaty, Disyan De Mario; Patimang, Andi (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2024)
Fakfak Regency is one of the areas in West Papua province which has quite abundant natural vegetable resources, one of which is red spinach. Red spinach (Amaranthus tricolor L.) is a vegetable that has a bitter taste so it is not liked by the public. Red spinach can be processed into snacks so that it is consumed more often by all groups. Red spinach vegetable snacks are made in the form of chips. This research aims to explain the effect of adding coating ingredients (mocaf, rice flour, and CMC) on the level of preference for red spinach chips. The research method used was a Completely Randomized Design (CRD) with one factor (mocaf concentration: rice flour: CMC) and 4 treatments consisting of P0 (50%: 0%: 0%); P1 (45%:5%:0.4%); P2 (40%:10%:0.8%); and P3 (35%:15%:1.2%). The data collection technique used an organoleptic test with a scale of 1 (very dislike) - 7 (very like) with 70 untrained panelists using color, aroma, taste and texture parameters. The data analysis technique used Chi-Square Tests and continued with the Duncans Multiple Range Test (DMRT) with a significance level of 95%. Determination of the best formula for red spinach chips processed using the De Garmo method in the form of an effectiveness index with a weighting procedure. The results of this study show that the addition of coating ingredients (mocaf, rice flour, and CMC) on the level of preference for red spinach chips has no significant effect on the parameters of color, aroma, taste and has a significant effect on texture parameters. The best formula for red spinach chips is P3 treatment (35% mocaf: 15% rice flour: 1.2% CMC) with color preference values of 5.57 (almost like); aroma of 5.81 (almost like); taste of 6.21 (almost really like); and texture of 6.55 (almost really like)